THE EFFECT OF QUICK RATIO DEBT TO RATIO AND FIXED ASSETS TURNOVER ON FINANCIAL PERFORMANCE IN THE FOOD AND BEVERAGE SUB SECTOR OF MANUFACTURING COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE - Paringga, Aprilia Megawati; Kurniawati, O (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
The aims of this study were to anayzed the effect of Quick Ratio, Debt to Ratio, and Fixwd Assest Turnover on Financial Performance in the Food and Baverage Sub Sector of Manufacturing Companies Listed in Indonesian Stock Exchange. The sample in this study consisted of 20 companies into 54 financial reports and annual reports of 20 the food and beverage sub-sector of manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2018- 2020 using the purposive sampling method. The results of this study shows that the t-test calculation proves that partially Quick Ratio and Fixed Assets Turnover have no significant effect on Return On Assets, but for Debt to Equity Ratio partially have an effect on Return On Assets. The calculation of the F test results simultaneously proves that the Quick Ratio, Debt to Equity Ratio, and Fixed Assets Turnover have a significant effect on Return On Assets. The Coefficient of Determination test is known that the R square value is 0.328 or 32.8% which indicates that ROA can be explained by QR, DER and FATO while the remaining 67.2% is explained by other variables